(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article analyzes the phraseological units of the Belarusian literary language, combined with the presence of one-root lexeme components heaven, heavenly and the heavens, representing “the heaven concept”, which represents one fragment of the phraseological worldview of the Belarusians. It is established how the language and culture of the nation are combined in the images of phraseological units, how the images of phraseological units bring the cultural information when they are “read” and how the locally-spatial and theological paradigms of the heaven concept with the predominance of the former are reflected. The paper puts emphasis on therevealing the role and place of the lexemeheaven and its derivatives heavenly and the heavens, the creation of images of phraseological units with them for the expression of new meanings, as well as the reflection in the images of the phraseological units of the perception of heavenconcept by the human being for expressing characteristics and assessments of new nominations. The analysis of phraseological units representing the heaven concept tallows to reveal not only the new designation mostly abstract concepts and phenomena that are identified as the most important for the proper organization of human life and its relationships in the collective of people, but also to characterize and evaluate these concepts, phenomena and actions and thus to represent the rules and attitudes of people.